Identification and characterization of the poly(A)-binding proteins from the sea urchin: a quantitative analysis. - Drawbridge, J (1990)
Poly(A)-binding proteins (PABPs) are the best characterized messenger RNA-binding proteins of eucaryotic cells and have been identified in diverse organisms such as mammals and yeasts. The in vitro poly(A)-binding properties of these proteins have been studied intensively; however, little is known about their function in cells. In this report, we show that sea urchin eggs have two molecular weight forms of PABP (molecular weights of 66,000 and 80,000). Each of these has at least five posttranslationally modified forms. Both sea urchin PABPs are found in approximately 1:1 ratios in both cytoplasmic and nuclear fractions of embryonic cells. Quantification in eggs and embryos revealed that sea urchin PABPs are surprisingly abundant, composing about 0.6% of total cellular protein. This is 50 times more than required to bind all the poly(A) in the egg based on the binding stoichiometry of 1 PABP per 27 adenosine residues. We found that density gradient centrifugation strips PABP from poly(A) and therefore underestimates the amount of PABP complexed to poly(A)+ RNA in cell homogenates. However, large-pore gel filtration chromatography could be used to separate intact poly(A)-PABP complexes from free PABP. Using the gel filtration method, we found that the threefold increase in poly(A) content of the egg after fertilization is paralleled by an approximate fivefold increase in the amount of bound PABP. Furthermore, both translated and nontranslated poly(A)+ RNAs appear to be complexed to PABP. As expected from the observation that PABPs are so abundant, greater than 95% of the PABP of the cell is uncomplexed protein.